Cervical Spine Hyperextension and Altered Posturo-Respiratory Coupling in Patients With Obstructive Sleep Apnea Syndrome - Clavel, Louis; Rémy-Neris, Ségolène; Skalli, Wafa; Rouch, Philippe; Lespert, Yoann; Similowski, Thomas; Sandoz, Baptiste; Attali, Valérie (Frontiers in Medicine, 2020)
Obstructive sleep apnea syndrome (OSAS) is associated with postural dysfunction characterized by abnormal spinal curvature and disturbance of balance and walking, whose pathophysiology is poorly understood. We hypothesized that it may be the result of a pathological interaction between postural and ventilatory functions. Twelve patients with OSAS (4 women, age 53 years [51-63] (median [quartiles]), apnea hypopnea index 31/h [24-41]) were compared with 12 healthy matched controls. Low dose biplanar X-rays (EOS® system) were acquired and personalized three-dimensional models of the spine and pelvis were reconstructed. We also estimated posturo-respiratory coupling by measurement of respiratory emergence, obtaining synchronized center of pressure data from a stabilometric platform and ventilation data recorded by an optico-electronic system of movement analysis. Compared with controls, OSAS patients had cervical hyperextension with anterior projection of the head (angle OD-C7 12° [8; 14] vs 5° [4; 8]; p=0.002), and thoracic hyperkyphosis (angle T1-T12 65° [51; 71] vs 49° [42; 59]; p=0.039). Along the mediolateral axis: 1) center of pressure displacement was greater in OSAS patients, whose balance was poorer (19.2 mm [14.2; 31.5] vs 8.5 [1.4; 17.8]; p=0.008); 2) respiratory emergence was greater in the OSAS patients, who showed increased postural disturbance of respiratory origin (19.2% [9.9; 24.0] versus 8.1% [6.4; 10.4]; p=0.028). These results are evidence for the centrally-mediated and primarily respiratory origin of the postural dysfunction in OSAS. It is characterized by an hyperextension of the cervical spine with a compensatory hyperkyphosis, and an alteration in posturo-respiratory coupling, apparently secondary to upper airway instability.